Penerapan Model ASSURE Menggunakan Media Wordwall dalam Pembelajaran Teks Diskusi pada Peserta Didik Kelas IX - Jingga Jingga; Arfi Rinantari; Uli Laela Rahma; Vita Aprilia Kartikasari; Asep Purwo Yudi Utomo; Diyamon Prasandha (Jurnal Kajian Penelitian Pendidikan dan Kebudayaan, 2023)
Students in the digital era expect more learning using technology. This requires teachers to modify learning by applying technology in it. This study tries to apply the ASSURE learning model with the integration of Wordwall Games media which can be accessed on each student's device in class. The uses of Wordwall Games media match with the ASSURE model because it links technology. Wordwall Games is a game specially designed for learning. This game can improve motivation in students' learning, so that learning in the technological era become more effective and efficient. This research based on classroom action research on discussion text material using the ASSURE model using Wordwall media in class IX at SMP Negeri 9 Semarang which is targeted in 2 learning cycles. The results showed that there was an students enhancement motivation in 2 learning cycles of learning as evidenced by increased of student learning outcomes. This proves that the ASSURE model and Wordwall media are fit to be applied in Indonesian learning, especially in discussion text.